1999
DOI: 10.1037/0021-9010.84.6.986
|View full text |Cite
|
Sign up to set email alerts
|

Why visual and vocal interview cues can affect interviewers' judgments and predict job performance.

Abstract: Using videotaped interviews with 60 managers in utility companies, the authors found that a composite of vocal interview cues (pitch, pitch variability, speech rate, pauses, and amplitude variability) correlated with supervisory ratings of job performance (r = .18, p < .05). Using videotaped interviews with 110 managers in a news-publishing company, the authors found that the same composite of vocal cues correlated with performance ratings (r = .20, p < .05) and with interviewers' judgments (r-.20, p < .05) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 28 publications
5
134
0
Order By: Relevance
“…Our definitions for vocal cues follow directly from DeGroot and Motowidlo (1999). "Pitch" is the average fundamental frequency over an entire speech sample, and it represents how high or low a voice is.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our definitions for vocal cues follow directly from DeGroot and Motowidlo (1999). "Pitch" is the average fundamental frequency over an entire speech sample, and it represents how high or low a voice is.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research on vocal attractiveness has shown that personal reactions such as liking and trust mediate the relationship between vocal attractiveness and job performance evaluations of subordinates (DeGroot & Motowidlo 1999). Similarly, those personal reactions of followers have been studied in the leadership literature as follower effects (Conger et al 2000;Kirkpatrick & Locke 1996;Podsakoff, MacKenzie, Moorman, & Fetter 1990) and as mediating mechanisms in the relationship between leadership and followers' evaluations of leaders (Yukl 1989).…”
Section: The Mediating Effect Of Personal Reactionsmentioning
confidence: 99%
See 3 more Smart Citations